Surface tension driven aggregation of organic nanowires via lab in a droplet. Issue 23 (5th June 2018) - Gu, Jianmin; Yin, Baipeng; Fu, Shaoyan; Feng, Man; Zhang, Ziming; Dong, Haiyun; Gao, Faming; Zhao, Yong Sheng
Abstract : A simple surface tension driven aggregation of organic nanowires strategy was demonstrated for the fabrication of dandelion-like nanostructures with 1D nanowire as building blocks via lab in a droplet. Abstract : Directing the architecture of complex organic nanostructures is desirable and still remains a challenge in areas of materials science due to their structure-dependent collective optoelectronic properties. Herein, we demonstrate a simple and versatile solution strategy that allows surface tension to drive low-dimensional nanostructures to aggregate into complex structures via a lab in a droplet technique. By selecting a suitable combination of a solvent and an anti-solvent with controllable surface tension difference, the droplets can be automatically cracked into micro-droplets, which provides an aggregation force directed toward the centre of the droplet to drive the low-dimensional building blocks to form the special aggregations during the self-assembly process. This synthetic strategy has been shown to be universal for organic materials, which is beneficial for further optimizing the optoelectronic properties. These results contribute to gaining an insightful understanding on the detailed growth mechanism of complex organic nanostructures and greatly promoting the development of organic nanophotonics.